Analysis of Financial Performance on Stock Prices with Dividend Policy as a Moderation Factor - Gladisya Zafira Azzahra; Naelati Tubastuvi; Wida Purwidianti; Alfato Yusnar Kharismasyah (Agregat: Jurnal Ekonomi dan Bisnis, 2026)
This study aimed to analyze the effects of ROE, CR, DER, and TATO on stock prices, with dividend policy as a moderating variable, in consumer non-cyclical companies listed on the Indonesia Stock Exchange during 2021–2024. The sample was determined using a purposive sampling approach. Out of 131 listed firms, 33 companies met the criteria, yielding 132 firm-year observations.  A quantitative approach was applied through panel data regression using STATA 17. The results show that ROE, CR, and TATO have no effect, while DER has a positive effect on stock prices. DPR does not moderate the effects of ROE, CR, and TATO, but weakens the effect of DER. These findings indicate that investors pay more attention to capital structure than to other financial ratios and dividend policy in making investment decisions. Future research is recommended to include additional variables and expand the research period and sectors to obtain more comprehensive results